PENGARUH KUALITAS TEKNIS, KUALITAS FUNGSIONAL, CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH DAN DAMPAKNYA PADA LOYALITAS NASABAH (STUDI PADA NASABAH KREDIT KENDARAAN BERMOTOR (KKB) PADA BCA PONTIANAK) - B2041132036, OKTANTO (Universitas Tanjungpura, 2017)
Kredit Kendaraan Bermotor (KKB) BCA Pontianak is a product of BCA pontianak KKB financing provided by Bank Central Asia to customers who wish to apply for car financing. It’s seen from the rapid growth of the automotive world especially car in the area of Indonesia. Based on these, the banks began to develop one product on the name of Kredit Kendaraan Bermotor (KKB) BCA. This study aimed to determine the effect of service quality BCA described KKB financing through the variable technical quality, fungsional quality, corporate image on customer satisfaction and it’s impact on customers loyalty. Population in this research is the individual customer KKB BCA Pontianak which has a refinancing facility from 2013 to 2015 amounting to 1.421 customers. Sampling using the formula slovin respondents as many as 130 customers. Model of this research is explanatory research. Data analysis techniques using path analysis with SPSS (Statical package for social scienes) program version 17.0 for windows. Based on the data processing using path analysis, proved that the technical quality, functional quality, and corporate image influence on customer satisfaction and technical quality, functional quality, corporate image and customer satisfaction is also positive ang significant impact on customer loyalty. And customer satisfaction as an intervening variable. Keyword: Technical Quality,Functional Quality, Corporate Image, Customer Satisfaction and Customer Loyalty